Circulating Tumor Cells in Gastrointestinal Cancers: Current Status and Future Perspectives - Yang, Chaogang; Chen, Fangfang; Wang, Shuyi; Xiong, Bin (Frontiers in Oncology, 2019)
Circulating tumor cells (CTCs), which are now defined as the “break away” cancer cells that derive from primary- or metastatic-tumor sites and present in the bloodstream, are considered to be the precursors of metastases. Considering the key role of CTCs in cancer progression, researchers are committed to analyzing them in the past decades and many technologies have been proposed for achieving CTCs isolation and characterization with highly sensitivity and specificity until now. On this basis, clinicians gradually realize the clinical values of CTCs’ detection through various clinical studies. As a “liquid biopsy”, CTCs’ detection and measurement can supply important information for predicting patient’s survival, monitoring of response/resistance, assessment of minimal residual disease, evaluating distant metastasis, and sometimes, customizing therapy choices. Nowadays, eliminating CTCs of the blood circulation has been regarded as a promising method to prevent tumor metastasis. However, research on CTCs still faces many challenges. Herein, we present an overview to discuss the current concept of CTCs, summarize the available techniques for their detection, and provide an update on the clinical significance of CTCs in GI malignancies, especially focus on gastric and colorectal cancer.